2013
DOI: 10.1007/978-3-642-41004-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of Inorganic Polyphosphate Metabolism

Abstract: Inorganic polyphosphate (PolyP) is a linear polymer containing a few to several hundred orthophosphate residues linked by energy-rich phosphoanhydride bonds. Investigation of PolyP-metabolizing enzymes is important for medicine, because PolyPs perform numerous functions in the cells. In human organism, PolyPs are involved in the regulation of Ca(2+) uptake in mitochondria, bone tissue development, and blood coagulation. The essentiality of polyphosphate kinases in the virulence of pathogenic bacteria is a basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 114 publications
(169 reference statements)
0
19
0
Order By: Relevance
“…In mammalians, a long-chain endopolyphosphatase was purified from rat and bovine brain (Kumble and Kornberg, 1996), a human metastasis regulator protein H-prune was identified as a short-chain specific exopolyphosphatase (Tammenkoski et al, 2008), and mammalian intestinal alkaline phosphatase was characterized as a very active exopolyphosphatase (Lorenz and Schroder, 2001). In addition, 41% homology has been found between yeast exopolyphosphatase PP1 gene product and human acid sphingomyelinase-like phosphodiesterase (Duan, 2006; Kulakovskaya and Kulaev, 2013). In the colon, this enzyme may play anti-proliferative and anti-inflammatory roles via ceramide generation, reducing the lysophosphatidic acid formation, and inactivating the platelet-activating factor and mutations in its gene have been found in cancer cells of the intestines (Duan, 2006).…”
Section: What Is Inorganic Polyphosphate?mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalians, a long-chain endopolyphosphatase was purified from rat and bovine brain (Kumble and Kornberg, 1996), a human metastasis regulator protein H-prune was identified as a short-chain specific exopolyphosphatase (Tammenkoski et al, 2008), and mammalian intestinal alkaline phosphatase was characterized as a very active exopolyphosphatase (Lorenz and Schroder, 2001). In addition, 41% homology has been found between yeast exopolyphosphatase PP1 gene product and human acid sphingomyelinase-like phosphodiesterase (Duan, 2006; Kulakovskaya and Kulaev, 2013). In the colon, this enzyme may play anti-proliferative and anti-inflammatory roles via ceramide generation, reducing the lysophosphatidic acid formation, and inactivating the platelet-activating factor and mutations in its gene have been found in cancer cells of the intestines (Duan, 2006).…”
Section: What Is Inorganic Polyphosphate?mentioning
confidence: 99%
“…In the colon, this enzyme may play anti-proliferative and anti-inflammatory roles via ceramide generation, reducing the lysophosphatidic acid formation, and inactivating the platelet-activating factor and mutations in its gene have been found in cancer cells of the intestines (Duan, 2006). Interestingly, the human protein H-prune exhibits 91% homology with the sequences of yeast exopolyphosphatase PPX1 (Kulakovskaya and Kulaev, 2013). Furthermore, in some prokaryotes [such as Micrococcus luteus, Corynebacterium ammoniagenes (Fillipovich et al, 2000), Micrococcus flavus and Mycobacterium tuberculosis (Kawai et al, 2000)] NAD kinase catalyzes phosphorylation of NAD using both ATP and polyP as phosphoryl donors (Figure 3B) while E. Coli NAD kinase is not able to use polyP (Kawai et al, 2001).…”
Section: What Is Inorganic Polyphosphate?mentioning
confidence: 99%
“…One of the main functions of polyP is to act as a Pi reserve in both prokaryotes and in unicellular eukaryotes (Rao, Gomez‐Garcia, & Kornberg, ). However, high eukaryotes display lower amounts of cellular polyP and these polymers act presumably as regulators of energy and phosphorus metabolism (T. Kulakovskaya & Kulaev, ). Since the Pi levels are in opposite with the polyP levels, our results suggested that polyP was involved in the mitochondrial bioenergetics of T. castaneum .…”
Section: Resultsmentioning
confidence: 99%
“…PPXs have been best studied in S. cerevisiae ; after subfractionation of its mitochondria, it was revealed that both the membrane preparation and the soluble fraction possessed exopolyphosphatase activities in equal proportions (T. Kulakovskaya & Kulaev, ). In T. castaneum, mitochondrial subfractionation revealed membrane and soluble PPXs, as reported in yeast; however, most activities were determined in the soluble fraction (T. Kulakovskaya & Kulaev, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation